Education Policy Overcome Coronavirus, A Study of Indonesians - Muh Barid Nizarudin Wajdi; Iwan Kuswandi; Umar Al Faruq; Zulhijra Zulhijra; Khairudin Khairudin; Khoiriyah Khoiriyah (EDUTEC : Journal of Education And Technology, 2020)
The COVID-19 or Coronavirus that encircled Indonesia seems to be unmuted. Its massive and relatively fast spread makes people feel scared. Everyone is forced to remain at home to break the COVID-19 transmission chain. Mass agenda eliminated because of COVID-19 also the term work from home (WFH) so popular. COVID-19 also has a serious impact on the education sector in Indonesia. Here are some policies in the world of education taken by the Indonesian government in the emergency period of Coronavirus (COVID-19) year 2020. This article aims to discuss government policy, especially about the education policy to deal with Coronaviruses. The results showed that some government policies related to education in the time Coronavirus could minimize the spread of coronaviruses. These policies include online learning for school children, online lectures, national Examinations 2020 canceled, UTBK SBMPTN 2020 postponed, the implementation for SNMPTN still in review